Validity and Practicality of Geogebra Application-Based Mathematics Learning Tools to Train Visual-Spatial Intelligence - Hikmah, Rezkiyana (Insitut Agama Islam Negeri Kerinci, 2023)
An effective distance learning tool must be able to train students' spatial intelligence to help them develop visualization skills. Thus, this study aims to see the validity and practicality of GeoGebra application-based distance learning tools. This development research (R&D) uses a three-phase development approach based on Plomp Theory, which is divided into three stages: preliminary research, prototyping, and assessment. Validation and practicality questionnaires were used to obtain research data and analyzed with descriptive qualitative statistics. The results of the data analysis showed that the mathematics learning tools were evaluated with the